QUALITATIVE ANALYSIS OF AMDK AND AMIU AROUND UNIVERSITY OF MUHAMMADIYAH KUDUS - Yunita Rusidah; Lailatul Farikhah; Yayuk Mundriyastutik ((IJP) Indonesia Jurnal Perawat, 2021)
This study is intended to find the quality of bottled drinking water (AMDK) and drinking water (AMIU) sold around University of Muhammadiyah Kudus, in terms of organoleptic and microbiological parameters in drinking water according to SNI 01-3554-2006 and PMK No. 492 of  2010. The test is carried out using 10 sample of drinking water. They are 7 sample of AMDK (Ades, Airmu, Aqua, Cleo, Crystalin, Le mineral and Vit) and 3 sample of AMIU (Pasuruhan, Prambatan and Purwosari depots). The research consists of chemical physics which includes testing of TDS, pH, and three heavy metal elements which includes testing for the content of the elements Fe, Mn and Cl2 (chlorine), organoleptic and  mikrobiologis (TPC, presence of E. coli and total coliform).The results of research shows that of physical and chemical measurements, the total dissolved solid (TDS) results 0 for Airmu and Cleo (demineral) and below 500 ppm for 8 samples of mineral water, this is according with the TDS requirements of SNI, 10 ppm for demineralized and 500 ppm for mineral water. The results of the pH test or the degree of acidity are in normal pH, which are around 7 out of 9 samples and only one with an alkaline condition is 8.37, namely the sample from the Pasuruhan depot. The test for the presence of heavy metals, Fe, Mn, is in good condition, showing the number zero with the brand brand test kit. Whereas for testing the presence of chlorine content, the results were above the threshold, namely 0.05 ppm from the Pasuruhan depot water sample, 0.02 ppm from the Prambat depot and the Purwosari depot. This is not in accordance with SNI provisions for chlorine content of 0 ppm. The organoleptik of all samples is in normal condition. Whereas, microbiologically, the TPC results before dilution were only Cleo and Ades which were suitable for consumption because they were absent from bacterial contamination. While the TPC results after dilution, testing the difference between E. Coli and Total coliform resulted in 7 samples of bottled drinking water which were safe and feasible as drinking water according to SNI 01-3553-2006 and 3 samples AMIU does not fulfil PMK No. 492/2010, as drinking water requirements.Keywords: AMDK, AMIU, Organoleptic Quality, Microbiology